2022
DOI: 10.20473/jbe.v10i32022.227-236
|View full text |Cite
|
Sign up to set email alerts
|

Salt Taste Threshold as a Detection of Salt Intake in Hypertensive Individuals

Abstract: Background: High sodium consumption is one of the risk factors for hypertension. Excess salt intake may be affected by an individual’s ability to detected taste. However, decreased salt sensitivity can increase consumption of salty foods. Purpose: This review aims to analyze the salt taste threshold and its relation to salt intake among hypertensive and normotensive individuals. Methods: The review was conducted using five electronic databases and fourteen articles reporting on salt taste threshold, salt intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…Men have a higher chance of experiencing hypertension than women. The results of statistical tests in this study are different from the results of research by Fayasari and Cahyani, and there was no difference in the salty taste threshold between the control group and the hypertension group 17 . Another study by Kim showed no correlation between the detection or recognition of taste thresholds and systolic blood pressure 30 .…”
Section: Table 2 Frequency Distribution Of Salty Taste Thresholdscontrasting
confidence: 99%
See 1 more Smart Citation
“…Men have a higher chance of experiencing hypertension than women. The results of statistical tests in this study are different from the results of research by Fayasari and Cahyani, and there was no difference in the salty taste threshold between the control group and the hypertension group 17 . Another study by Kim showed no correlation between the detection or recognition of taste thresholds and systolic blood pressure 30 .…”
Section: Table 2 Frequency Distribution Of Salty Taste Thresholdscontrasting
confidence: 99%
“…Another study by Kim showed no correlation between the detection or recognition of taste thresholds and systolic blood pressure 30 . This study's results align with the literature study conducted by Sari et al who found a correlation between the salt taste threshold and hypertension as measured by questionnaires and 24hour urinary sodium excretion 34 . However, a study by Sawai et al shows a relationship between the saltiness threshold and consuming foods containing high salt 35 .…”
Section: Table 2 Frequency Distribution Of Salty Taste Thresholdssupporting
confidence: 91%
“…According to Han et al (14), a high intake of food salt had the most vital role in the incidence of hypertension. In studies related to salt intake, it is important to distinguish between the term's "salt" and "sodium" (12,13). It was commonly acknowledged that 1 gram of salt composed of 40% sodium and 60% chloride.…”
Section: Variable Excess Salt Consumptionmentioning
confidence: 99%